MANAGEMENT OUTCOMES OF EXTRA ABDOMINAL FIBROMATOSIS AMONG ADULT PATIENTS TREATED AT A TERTIARY CARE HOSPITAL - Umer, Masood; Saeed, Javeria; Anwer, Irfan; Zahid, Nida; Durrani, Younus (Journal of Ayub Medical College Abbottabad, 2019)
Background: Aggressive fibromatosis or desmoid fibromatosis is a soft tissue neoplasm which is non-metastatic in nature. Among all soft tissue tumours, it comprises of 3% cases and is more common in females as compared to males. Objective of our study was to evaluate the treatment outcomes of extra abdominal fibromatosis in patients who were treated in our setup and determine the recurrence patterns. Methods: It is retrospective cohort of 15 patients that were treated in section of Orthopaedics, department of surgery, Aga Khan University hospital, Karachi from January 1990 to December 2015. It included all adult patients of age >18 years with biopsy proven extra abdominal aggressive fibromatosis. Data was analysed on SPSS 22 version. Results: Out of 15 patients, there were 7 males (46.7%) and 8 females (53.3%). Median age was 22 years. Majority of patients [10 (66.6%)] had upper limb lesion. On initial biopsy we had 11 (73.3%) cases of primary fibromatosis while 2 (13.3%) were recurrent and 2 (13.3%) were spindle cell carcinoma. The median (IQR) follow-up time of the participants was 3 (2-3) months. Complications occurred in 8 (53.3%) patients. A significant difference was observed in the haemoglobin levels before and after surgery with a mean difference of 2.74 (p-value<0.001). Recurrence of disease occurred in 4 (26.7%) patients and all of these patients who had recurrence underwent 2nd surgery versus 1 of the participants who had second surgery without recurrence and this was a significant difference (p value <0.004). Conclusion: Extra abdominal fibromatosis is commonly found among younger age groups, affecting females more as compared to males. Less than half of the patients had recurrence of disease in our study and intra-operative and post-operative complications are common surgical outcomes and our study results are compatible with previously reported literature. Keywords: Aggressive fibromatosis; Desmoid fibromatosis; adult patients; extra-abdominal